Educators in the Perspective of Islamic Education - Faqih Faizal Rahman (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
Educators are those who are directly involved in fostering, directing and educating students. Education is a top priority in Islam for educators, students and those involved in education. The term educator in Islam is referred to by terms such as muadid, murabi and mualim. The ultimate goal of Islamic education is the creation of Insan Kamil, and to realize this goal in Islamic education, educators have the responsibility to guide students in the intended direction. Their task is not only to provide and incorporate knowledge, but also to internalize students' values, so that as educators they can maximize their potential, both emotionally and cognitively. by trying to maximize their potential. Also called the potential of taste, creativity, and initiative, as well as psychomotor potential.